The Subjection of the Creature to the Futility of Idolatry: The Scope and Application of Romans 8:19–22 - Perriman, Andrew (Bulletin for biblical research, 2023)
What Paul has to say in Rom 8:19-22 about the subjection of ἡ κτίσις to futility, its bondage to corruption, and its groaning in pain is usually read as a statement about the general condition of creation, ruined by the sin of Adam as indicated in Rom 5:12, which, along with believers in Jesus, yearns for final restoration. The argument put forward here will be that the conceptual frame for the passage is furnished not by the story of the fall but by the more focused and characteristically Hellenistic-Jewish polemic against "Greek" idolatry developed in Rom 1:19-23. What troubles Paul as a pious Jew in the Mediterranean world is the subjection of the material of creation—wood, stone, gold, silver—to futile religious practices that result in the corruption of life. The whole of creation groans in solidarity with the abused "creature," but in the "present time" there is also a groaning community that bears confident witness to the approaching end of the impious pagan order.